Reperfusion Strategies in Acute Myocardial Infarction: State of the Art - Rangel,Fernando Oswaldo Dias (2022)
Abstract ST elevation myocardial infarction (STEMI) is a highly prevalent condition worldwide. Reperfusion therapy is strongly associated with the prognosis of STEMI and must be performed with a high standard of quality and without delay. A systematic review of different reperfusion strategies for STEMI was conducted, including randomized controlled trials that included major cardiovascular events (MACE), and systematic reviews in the last 5 years through the PRISMA ( Preferred Reporting Items for Systematic Reviews and Meta-Analysis) methodology. The research was done in the PubMed and Cochrane Central Register of Controlled Trials databases, in addition to a few manual searches. After the exclusion criteria were applied, 90 articles were selected for this review. Despite the reestablishment of IRA patency in PCI for STEMI, microvascular lesions occur in a significant proportion of these patients, which can compromise ventricular function and clinical course. Several therapeutic strategies – intracoronary administration of nicorandil, nitrates, melatonin, antioxidant drugs (quercetin, glutathione), anti-inflammatory substances (tocilizumab [an inhibitor of interleukin 6], inclacumab, P-selectin inhibitor), immunosuppressants (cyclosporine), erythropoietin and ischemic pre- and post-conditioning and stem cell therapy – have been tested to reduce reperfusion injury, ventricular remodeling and serious cardiovascular events, with heterogeneous results: These therapies need confirmation in larger studies to be implemented in clinical practice